Karrierewege zur Professur an einer Fachhochschule - Diallo-Ruschhaupt, Ursula; Plaumann, Susanne; Dombrowski, Eva-Maria (Schriftenreihe des Gender- und Technik-Zentrums (GuTZ) der Beuth Hochschule für Technik Berlin "Gender Diskurs", 2017)
The recruitment of University of Applied Sciences professors has been intensively discussed by science organisations since 2016. Has Beuth University of Applied Sciences Berlin succeeded in significantly increasing the proportion of women among FH professorships within the free appointment corridors and in establishing a "place to be" strategy? This publication discusses the point.